2010
DOI: 10.2466/pms.110.2.463-468
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Workplace Behavior among Municipal Employees in Spanish and Finnish Cities: A Cross-National Comparison

Abstract: A comparative study measuring differences in the prevalence of conflicts, burnout, bullying, and sexual harassment among municipal employees between two European cities was conducted using a self-report instrument, the Psychosocial Workplace Inventory. The cities were Valencia, Spain (n=1,007) and Vaasa, Finland (n=1,979). Significant differences were found between reports of employees from the two cities. The Spanish employees reported higher scores on every type of dysfunctional workplace behavior measured: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…El presente estudio tuvo tres objetivos (i) determinar la experiencia previa y actual de bullying en el trabajo entre una muestra de 295 adultos que retomaron la educación terciaria, (ii) profundizar en la 'hipó-tesis del ambiente de trabajo ' (Einarsen, Raknes, y Matthiesen, 1994; Mc Guckin, Lewis, y Shevlin, under review) como un antecedente en el proceso de WPB, examinando la relación entre 'el ambiente psicosocial en el lugar de trabajo' y la exposición a WPB (varhama & Björkqvist, 2004a, b;varhama et al, 2010), y (iii) explorar la relación entre la exposición al WPB y las variables de actitudes *Correspondencia: Conor Mc Guckin, School of Education, Trinity College Dublin, Dublin 2, Ire-…”
Section: Experiencias De Bulling En El Lugar De Trabajo Entre Estudiaunclassified
See 2 more Smart Citations
“…El presente estudio tuvo tres objetivos (i) determinar la experiencia previa y actual de bullying en el trabajo entre una muestra de 295 adultos que retomaron la educación terciaria, (ii) profundizar en la 'hipó-tesis del ambiente de trabajo ' (Einarsen, Raknes, y Matthiesen, 1994; Mc Guckin, Lewis, y Shevlin, under review) como un antecedente en el proceso de WPB, examinando la relación entre 'el ambiente psicosocial en el lugar de trabajo' y la exposición a WPB (varhama & Björkqvist, 2004a, b;varhama et al, 2010), y (iii) explorar la relación entre la exposición al WPB y las variables de actitudes *Correspondencia: Conor Mc Guckin, School of Education, Trinity College Dublin, Dublin 2, Ire-…”
Section: Experiencias De Bulling En El Lugar De Trabajo Entre Estudiaunclassified
“…Considering that the purpose of research designed to identify antecedent 'trigger' variables in the bullying process is to aid 'risk assessment' and 'risk management' in terms of intervention and prevention (Cox, 2005), Mc Guckin et al (under review) suggest that aspects of the 'psychosocial work environment' (e.g., conflict, burnout, work harassment, work atmosphere, work stress, sexual harassment, and alcohol abuse) may also act as antecedent variables in the bullying process. varhama and Björkqvist (2004a, b) andvarhama et al (2010) have demonstrated the relationship between workplace bullying and these aspects of the psychosocial work environment among samples of Finnish, Polish, and Spanish employees. One of the aims of the present research is to extend this previous research by exploring the relationship between these hypothesised psychosocial work environment variables and experiences of bullying behaviours.…”
Section: Antecedents Of Workplace Bullying: the Role Of The Work Envimentioning
confidence: 99%
See 1 more Smart Citation
“…Within the framework of this type of comparison, we mention part of the results of this study: Among 1,919 Finnish workers from the city of Vasa and 1,007 Spanish workers from the city of Valencia, a prevalence of 15% and 18%, respectively, was found (Varhama, Baguena, Toldos, Beleña, Roldan, Diaz, Österman, & Björkqvist, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we will also present the results obtained from each of these methods separately, keeping in mind that the exclusive use of the perceived victimization method in this study leads us to evaluate victimization by bullying at some time in the working life of the participant and not during the last six months, as is the case when the exposure to bullying behaviors method is used. The perceived victimization method was the method used in the results presented by Varhama et al (2010).…”
Section: Introductionmentioning
confidence: 99%